Vozes da maré: extensão popular e a população marisqueira de Cabedelo-PB - Lima, Bruna Alice Taveira de (2019)
The extension appears as non-formal education that goes beyond the walls of the institution and regular education. However, a gnosiological definition of the term identifies it as an authoritarian way when limited to a mere generator of knowledge. The same extension, when it adopts the prerogatives of popular education, converts itself in a wider perspective: it is assumed as a methodology that considers popular technical knowledge and backgroun, usually acquired through informal education, through the oral tradition of Family or Community cultures passed on over generations. Artisanal fishing is a profession, but it is also a popular culture and it is traditionally learnet by the new generations. Considering the core idea that the extension is redesigned when the idea concept of popular, this research aims to answer to what extent an extension course can be understood as popular extension and what are the resulting objective and subjective. To this end, the pioneer Course on Qualification for shellfish collectors from Cabedelo in 2007 was analyzed. In order to achieve this, interviews were applied with the participants of that action, managers, social actors and leaders who participated the development of the course. Still, as a qualitative scope, it has considered the theoretical assumptions of oral history, with the objective of telling the life trajectories of the instution offering and also the individuals attended by the given course. Throughout this study, it has been identified aspects aspects of the action that confirms that it can be understood as popular extension and that the participating community suffered positive changes after the pioneer experience of that project.